INVESTIGATION OF THE STRENGTH AND DUTNESS OF REINFORCED CONCRETE BEAMS WITH GLASS COMPOSITE REINFORCEMENTS - Solijonov Foziljon Sodiqjon ugli; Xalimov Abbosbek Oybek ugli (Journals Park Publishing, 2022)
This article describes the analysis of the results of the research conducted on the study of the work of composite reinforced elements, which are widely used in the restoration of concrete structures in the buildings and structures currently being built in the Republic of Uzbekistan and in foreign countries.
Keywords: composite, basalt, concrete, flexibility, strength, messura, polymer.